High moisture corn silage in the feeding of broiler chickens - Sartori, José Roberto (Pesquisa Agropecuaria Brasileira, 2002)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0;} @font-face {font-family:"\@Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} p {margin-right:0cm; mso-margin-top-alt:auto; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Arial Unicode MS";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The objective of this work was to evaluate the high moisture corn silage (HMCS) as ingredient in broiler chicken diets, in total substitution to dried corn (DC) on performance, carcass yield, organ weights and intestinal morphology. In the first trial, 600 one-day-old male chicks Ross were distributed in randomized blocks, with six treatments (A: DC of 1-42 days; B: HMCS of 1-42 days; C: HMCS of 1-7 days and DC of 8-42 days; D: HMCS of 1-14 days and DC of 15-42 days; E: HMCS of 1-21 days and DC of 22-42 days; F: DC + water of 1-42 days), with four replications of 25 poultry each. In the second trial, 24 male chicks Ross were utilized, distributed randomized in two treatments (with and without HMCS) and twelve replications each. The HMCS up to the age of 21 days did not interfere in the poultry performance and in the carcass yield at the age of 42 days. Broilers fed with HMCS presented higher relative weight of the liver, lower width of duodenum and ileum villus, higher height of the jejunum villus at 21 and lower depth of crypt in the duodenum and ileum at the age of 42 days. The HMCS can be considered an ingredient of broiler chicken diets up to the age of 21 days, for not interfering on the poultry final weight, on carcass yield and organ weights.